Legal Protection for Victims of Online Begging Exploitation Based on Circular Letter No. 2 of 2023 - Ariij Salsabil Alamsyah; Devita Gloria Ardida; Raushani Nadzifa Yahya (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
The rapid advancement of technology and globalization have notably influenced socio-economic dynamics in Indonesia where poverty persists despite broader access to digital information. A pressing concern emerging from this context is the phenomenon of online begging, predominantly conducted through platforms such as TikTok, where individuals or groups are begging for virtual gifts that can be monetised. This practice often preys upon at-risk groups, particularly children, the elderly, and individuals with disabilities, raising significant ethical and legal implications. This research uses a statute approach, conceptual approach, and case study methodology to critically discuss the legal protections available for victims of online begging in light of Circular Letter No. 2 of 2023. The findings suggest that online begging can be classified as a form of exploitation according to Law No.21 of 2007, thereby rendering the involved parties potentially culpable under Article 504 of the Penal Code. While the Circular Letter delineates preventive measures and guidelines for victim protection, the enforcement of these provisions is impeded by systemic issues, including pervasive poverty and inadequate educational opportunities. This research advocates for the establishment of a robust framework that integrates legal enforcement, public awareness campaigns, and socio-economic initiatives to address online begging effectively. Key recommendations include the formulation of enforceable policies, the enhancement of victim programs, and the tackling of underlying issues through education and poverty alleviation strategies.